EFEK MODERASI UKURAN PERUSAHAAN PADA PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN (Studi pada Perusahaan-Perusahaan Emiten yang Terdaftar Pada LQ 45 Periode Agustus 2014 s/d Januari 2015) - Surjadi, Christy; Tobing, Rudolf L. (Manajemen Bisnis Kompetensi, 2016)
ABSTRACT Firm value is certain conditions as an overview of public trust in a company that can be seen from the quality of the profit generated. However, earnings quality assessment information often does not reflect the actual company performance. This research method uses descriptive research with causative approach. The objects of this research are companies which listed in LQ45 index, and data collection techniques using secondary data from the Indonesia Stock Exchange website. Data analysis technique used is ordinary least square with interaction/moderated regression analysis. The result of this research shows that the size of board of directors has no significant positive effect on the firm value. The size of company assets does not significantly moderate the positive effect of the size of the board of directors to the firm value. There are significant positive influences of the independent board size and the size of audit committee to the firm value. Finally, the size of company assets significantly moderate the positive effect of independent board size and the size of the audit committee to the firm value. Keywords: good corporate governance, size of company assets, firm value, audit committe, moderated regression analysis, LQ45